The proteoglycan biglycan enhances antigen-specific T cell activation potentially via MyD88 and TRIF pathways and triggers autoimmune perimyocarditis - Popovic, Zoran V.; Wang, Shijun; Papatriantafyllou, Maria; Kaya, Ziya; Porubsky, Stefan; Meisner, Maria; Bonrouhi, Mahnaz; Burgdorf, Sven; Young, Marian F.; Schaefer, Liliana; Gröne, Hermann-Josef (The journal of immunology, 2011)
Biglycan is a proteoglycan ubiquitously present in extracellular matrix of a variety of organs, including heart, and it was reported to be overexpressed in myocardial infarction. Myocardial infarction may be complicated by perimyocarditis through unknown mechanisms. Our aim was to investigate the capacity of TLR2/TLR4 ligand biglycan to enhance the presentation of specific Ags released upon cardiomyocyte necrosis. In vitro, OVA-pulsed bone marrow-derived dendritic cells from wild-type (WT; C57BL/6) and TLR2-, TLR4-, MyD88-, or TRIF-deficient mice were cotreated with LPS, biglycan, or vehicle and incubated with OVA-recognizing MHC I- or MHC II-restricted T cells. Biglycan enhanced OVA-specific cross-priming by >80% to MHC I-restricted T cells in both TLR2- and TLR4-pathway-dependent manners. Accordingly, biglycan-induced cross-priming by both MyD88- and TRIF-deficient dendritic cells (DCs) was strongly diminished. OVA-specific activation of MHC II-restricted T cells was predominantly TLR4 dependent. Our first in vivo correlate was a model of experimental autoimmune perimyocarditis triggered by injection of cardiac Ag-pulsed DCs (BALB/c). Biglycan-treated DCs triggered perimyocarditis to a comparable extent and intensity as LPS-treated DCs (mean scores 1.3 ± 0.3 and 1.5 ± 0.4, respectively). Substitution with TLR4-deficient DCs abolished this effect. In a second in vivo approach, WT and biglycan-deficient mice were followed 2 wk after induction of myocardial infarction. WT mice demonstrated significantly greater myocardial T lymphocyte infiltration in comparison with biglycan-deficient animals. We concluded that the TLR2/4 ligand biglycan, a component of the myocardial matrix, may enhance Ag-specific T cell priming, potentially via MyD88 and TRIF, and stimulate autoimmune perimyocarditis.